The Rise Of Telemedicine: Transforming Healthcare Delivery (The Research of Medical Science Review, 2023)
This scholarly article looks at the transformative impact of telemedicine on healthcare delivery. With technological advancements, the rise of telemedicine has revolutionized the traditional healthcare landscape, providing innovative solutions for patient care, access and overall healthcare system efficiency. This article examines the evolution of telemedicine, its key components, its challenges, and the potential it holds to reshape the future of healthcare delivery. Through a comprehensive analysis of existing literature and case studies, this article aims to contribute to the growing body of knowledge surrounding the role of telemedicine in improving accessibility, affordability and quality of care health.Keywords:Telemedicine, healthcare delivery, technology, virtual health, remote patient monitoring, telehealth, digital health, telecommunications, patient-centered care, healthcare transformation.